2016
DOI: 10.1186/s12929-016-0235-6
|View full text |Cite
|
Sign up to set email alerts
|

Stearoyl-CoA desaturase indexes and n-6/n-3 fatty acids ratio as biomarkers of cardiometabolic risk factors in normal-weight rabbits fed high fat diets

Abstract: BackgroundBiomarkers for cardiometabolic risk (CMR) factors would be important tools to maximize the effectiveness of dietary interventions to prevent cardiovascular diseases. Thus, the aim of this work was to analyze stearoyl-CoA desaturase (SCD) indexes and n-6/n-3 fatty acids (FA) ratio as biomarkers of CMR induced by feeding rabbits on high fat diets (HFDs).MethodsRabbits were fed either regular diet or 18 % fat in regular diet (HFD) or 1 % cholesterol diet (HD) or diet containing 1 % cholesterol and 18 % … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 34 publications
0
14
0
Order By: Relevance
“…As mentioned by Alarcón et al [ 60 ], the symptoms cited below are also part of metabolic syndrome. For Hunter et al [ 33 ], metabolic syndrome (MetS) is associated with enhanced oxidative stress.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…As mentioned by Alarcón et al [ 60 ], the symptoms cited below are also part of metabolic syndrome. For Hunter et al [ 33 ], metabolic syndrome (MetS) is associated with enhanced oxidative stress.…”
Section: Discussionmentioning
confidence: 95%
“…For Hunter et al [ 33 ], metabolic syndrome (MetS) is associated with enhanced oxidative stress. Alarcón et al [ 60 ] mentioned a cardiometabolic risk with such parameter variations.…”
Section: Discussionmentioning
confidence: 99%
“…The products of SCD are major substrates for the biosynthesis of endogenous polyunsaturated fatty acids (PUFAs) and complex lipids such as triglycerides, phospholipids, cholesterol esters, and wax esters [2]. The ratio of SFAs to MUFAs can in uence a broad spectrum of cellular functions; thus, the content and distribution of SFAs and MUFAs within the cell must be tightly controlled by SCD [3]. Furthermore, SCD is an integral membrane protein of the endoplasmic reticulum, where it undergoes rapid turnover in response to a variety of nutritional and hormonal signals [4] and has served a vital metabolic function during evolution [5].…”
Section: Introductionmentioning
confidence: 99%
“…Research in recent years has revealed the in uence of SCD on membrane uidity, lipid metabolism, and energy metabolism [6][7][8]. Therefore, SCD has been identi ed as an important metabolic control point and is emerging as a promising therapeutic target in the treatment of obesity, diabetes, and other metabolic diseases [3,9]. Moreover, some studies point to SCD as a main factor in the control of cancer cell growth [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, current western fatty acid intake follows a trend towards higher n-6 to n-3 proportion, and epidemiologic studies indicate a consumption of ~1:16 (n-3/n-6) by these populations. While ratios of up to 1:6 or lower suggest beneficial long-term effects, 1:10 or greater proportions are indicative of future adverse consequences [17].…”
Section: Chlorella Is Rich In Polyunsaturated Fatty Acidsmentioning
confidence: 99%